Pengaruh Teman Sebaya terhadap Minat Belajar Siswa Kelas VII MTs Yakti Mangunrejo Kecamatan Tegalrejo Kabupaten Magelang - Yahdi Nur Falah; Nurus Sa’adah (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
The problem of this research is that there are students who are still indifferent to the assignments given, this is because of the lack of student interest in learning. This study aims to obtain accurate information and data regarding the influence of peers on students' learning interest in Arabic subjects. The approach used in this research is correlative quantitative. The population in this study were seventh grade students at MTs Yakti Mangunrejo, Tegalrejo District, Magelang Regency. The primary data collection of respondents was carried out by means of a survey. Data analysis includes normality test, linearity test and hypothesis testing. Pearson product moment correlation analysis was used in hypothesis testing by applying peer influence as an independent variable and learning interest as the dependent variable through the help of the IMB SPSS Statistics 23 software. Yati Mangunrejo, Tegalrejo District, Magelang Regency with a strong category. This can be seen from the correlations table, the value of sig (2-tailed = 0.000) < 0.025.